2018
DOI: 10.1016/j.jbi.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of medical conditions: Exposing patterns through probabilistic topic modeling of snomed codes

Abstract: Patients associated with multiple co-occurring health conditions often face aggravated complications and less favorable outcomes. Co-occurring conditions are especially prevalent among individuals suffering from kidney disease, an increasingly widespread condition affecting 13% of the general population in the US. This study aims to identify and characterize patterns of co-occurring medical conditions in patients employing a probabilistic framework. Specifically, we apply topic modeling in a non-traditional wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Ornstein et al estimated prevalence and multi-morbidity of 24 chronic conditions from an EHR database covering primary care practices 15 . Bhattacharya et al reported patterns of co-occurring conditions in patients with kidney disease by applying topic modeling on SNOMED codes 16 . Researchers who have access to an Observational Medical Outcomes Partnership (OMOP) database can use the open web applications ACHILLES and ATLAS to access useful statistics and scientific analyses, including counts per concept, prevalence rates, and frequencies of records per person 17 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Ornstein et al estimated prevalence and multi-morbidity of 24 chronic conditions from an EHR database covering primary care practices 15 . Bhattacharya et al reported patterns of co-occurring conditions in patients with kidney disease by applying topic modeling on SNOMED codes 16 . Researchers who have access to an Observational Medical Outcomes Partnership (OMOP) database can use the open web applications ACHILLES and ATLAS to access useful statistics and scientific analyses, including counts per concept, prevalence rates, and frequencies of records per person 17 .…”
Section: Background and Summarymentioning
confidence: 99%
“…The most common phenotypes are summarized in Figure 3 and include chronic conditions as well as adverse drug events. Social determinants of health such as marital status and homelessness were considered in 7 of the 106 articles [25][26][27][28][29][30][31], while more nuanced phenotypes such as disease severity (n = 5, 4.7%) [32][33][34][35][36] and disease subtypes (n = 19, 17.9%) [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] are emerging areas of focus. We also classified each phenotype as either binary (eg.…”
Section: Phenotypesmentioning
confidence: 99%
“…In contrast to the previously mentioned approaches, unsupervised learning is primarily used for phenotype discovery [151]. 20 articles developed unsupervised models, with a majority using latent Dirichlet allocation (LDA) [38,41,43,46,48], matrix or tensor factorization [40,44,52], and hierarchical clustering [45,47,[49][50][51] (Supplementary Material Table S12). A deep autoencoder was used to discover depression and suicidal ideation patterns [47].…”
Section: Unsupervised Learningmentioning
confidence: 99%
“…Recently, topic models have been applied in the health domain. In [4] applied LDA model to find associations across SNOMEDCT codes diagnoses in patients with kidney disease. Also, [5] used LDA to identify 25 phenotypes topics from information of two healthcare systems.…”
Section: Introductionmentioning
confidence: 99%